Determinant Factors of Public Acceptance of Stress Management Apps: Survey Study - Apolinário-Hagen, Jennifer (JMIR Ment Health, 2019)
BACKGROUND: Chronic stress is a major public health concern. Mobile health (mHealth) apps can help promote coping skills in daily life and prevent stress-related issues. However, little is known about the determinant factors of public acceptance of stress management in relation to preferences for psychological services. OBJECTIVE: The aim of this survey study was to (1) assess determinant factors of public acceptance (behavioral use intention) of stress management apps based on an adapted and extended version of the Unified Theory of Acceptance and Use of Technology (UTAUT) model and (2) explore preferences for mHealth apps compared with other mental health services. METHODS: Using convenience sampling, participants completed a multiscale 54-item Web-based survey. Based on significant correlations with acceptance, hierarchical stepwise regression analysis was performed within three blocks: (1) background and stress-related control variables, (2) beliefs and attitudes toward using mHealth, and (3) the core UTAUT determinants. The preference for mHealth apps in comparison with nine other mental health services (operationalized as readiness to use) was analyzed using paired t tests. RESULTS: Of 141 participants, nearly half (69/141, 48.9%) indicated prior mHealth use. Acceptance of stress coping apps was moderate (mean 3.10, SD 1.03, range 1-5). Hierarchical stepwise regression including four of 11 variables (R(2)=.62; P=.01, f(2)=1.63) identified positive attitudes toward using mHealth for stress coping (beta=0.69, P<.001, 46% R(2) increase above block 1, f(2)=0.85), skepticism/perceived risks (beta=−0.14, P=.01, f(2)=0.16), and stress symptoms (beta=0.12, P=.03, f(2)=0.14) as significant predictors of acceptance. UTAUT determinants added no predictive contribution beyond attitudes (all P>.05, R(2) increase of 1%), whereas post hoc analysis showed significant R(2) increases of attitudes and skepticism/perceived risks beyond UTAUT determinants (all P<.001, R(2) increase of 13%). The readiness to use apps was equivalent to or significantly higher than most service types, but lower than information websites. CONCLUSIONS: Attitudes may be at least as predictive for the acceptance of stress management apps as for more elaborated outcome beliefs. Efforts aimed at improving the public adoption of mHealth could put more emphasis on the pleasant aspects of app use, address misconceptions, offer stress screening tools on health websites, and increase options to try high-quality apps.